6-Gingerol alleviates exaggerated vasoconstriction in diabetic rat aorta through direct vasodilation and nitric oxide generation - Ghareib SA; El-Bassossy HM; Elberry AA; Azhar A; Watson ML; Banjar ZM (Dove Medical Press, 2015)
Salah A Ghareib,1 Hany M El-Bassossy,1,2 Ahmed A Elberry,3,4 Ahmad Azhar,5 Malcolm L Watson,6 Zainy Mohammed Banjar7 1Department of Pharmacology and Toxicology, Faculty of Pharmacy, King Abdulaziz University, Jeddah, Saudi Arabia; 2Department of Pharmacology, Faculty of Pharmacy, Zagazig University, Zagazig, Egypt; 3Department of Clinical Pharmacy, Faculty of Pharmacy, King Abdulaziz University, Jeddah, Saudi Arabia; 4Department of Pharmacology, Faculty of Medicine, Beni Suef University, Beni Suef, Egypt; 5Department of Pediatric Cardiology, Faculty of Medicine, King Abdulaziz University, Jeddah, Saudi Arabia; 6Department of Pharmacy and Pharmacology, University of Bath, Bath, UK; 7Department of Clinical Biochemistry, Faculty of Medicine, King Abdulaziz University, Jeddah, Saudi Arabia Abstract: The aim of the present study is to investigate the effect and potential mechanism of action of 6-gingerol on alterations of vascular reactivity in the isolated aorta from diabetic rats. Male Wistar rats were divided into two experimental groups, control and diabetics. Diabetes was induced by a single intraperitoneal injection of streptozotocin (50 mg kg-1), and the rats were left for 10 weeks to develop vascular complications. The effect of in vitro incubation with 6-gingerol (0.3–3 µM) on the vasoconstrictor response of the isolated diabetic aortae to phenylephrine and the vasodilator response to acetylcholine was examined. Effect of 6-gingerol was also examined on aortae incubated with methylglyoxal as an advanced glycation end product (AGE). To investigate the mechanism of action of 6-gingerol, the nitric oxide synthase inhibitor Nω-nitro-L-arginine methyl ester hydrochloride (100 µM), guanylate cyclase inhibitor methylene blue (5 µM), calcium-activated potassium channel blocker tetraethylammonium chloride (10 mM), and cyclooxygenase inhibitor indomethacin (5 µM) were added 30 minutes before assessing the direct vasorelaxant effect of 6-gingerol. Moreover, in vitro effects of 6-gingerol on NO release and the effect of 6-gingerol on AGE production were examined. Results showed that incubation of aortae with 6-gingerol (0.3–10 µM) alleviated the exaggerated vasoconstriction of diabetic aortae to phenylephrine in a concentration-dependent manner with no significant effect on the impaired relaxatory response to acetylcholine. Similar results were seen in the aortae exposed to methylglyoxal. In addition, 6-gingerol induced a direct vasodilation effect that was significantly inhibited by Nω-nitro-L-arginine methyl ester hydrochloride and methylene blue. Furthermore, 6-gingerol stimulated aortic NO generation but had no effect on AGE formation. In conclusion, 6-gingerol ameliorates enhanced vascular contraction in diabetic aortae, which may be partially attributed to its ability to increase the production of NO and stimulation of cyclic guanosine monophosphate. Keywords: diabetes, 6-gingerol, vasorelaxant, nitric oxide, advanced glycation end products, vascular complications